Protein and mineral metabolites for dairy cows during the transition period under tropical conditions. / metabolitos proteicos y minerales en vacas lecheras en período de transición bajo condiciones tropicales (2012)
In bovines, the transition period goes from the last three prepartum weeks to the first three postpartum weeks. This period is characterized by the metabolic adaptation of lipids, carbohydrates, minerals and proteins that try to balance the low intake of dry matter and the beginning of the secretion of milk. These changes are regulated by corticosteroids that are released at the time of birth. Some metabolites show noticeable changes in their blood concentration during this stage, which can lead to sanitary, reproductive and productive problems. The objective of the present work was to analyse the homeostasis in the transitional period, by determining the concentration of protein indicators, and some macrominerals, in dairy cows from two breeds under lowtropic conditions. The work was carried out in two commercial farms with similar management conditions in the Colombian south eastern region, in a agro-ecological zone of tropical dry forest according to Holdridge (1987), situated at 1,050 masl, with an average temperature of 23 ºC and an annual rainfall of 1200 mm bimodally distributed. The feed consisted of Bermuda grass (Cynodon nlemfuensis). The present work used seven Holstein cows and seven Hartón del Valle cows, from which blood samples were taken by coccygeal venepuncture in vacuum tubes, with heparin as anticoagulant and without anticoagulant, during the transition period, and up to the 60th day after delivery. A total of 156 samples were analysed. The following values were determined: total protein, albumin, globulin and urea; macro-minerals such as Ca, P and Mg and the cortisol hormone. The average values found for the Holstein breed were: total protein 66.7 g L-1, albumin 37.6 g L-1, globulins 27.7 g L-1, urea 6.11 mmol L-1, Ca 2.21 mmol L-1, P 1.87 mmol L-1, Mg 1.03 mmol L-1 and cortisol 33.2 nmol L-1. For the Hartón del Valle breed the following average values were found: total protein 57.7 g L-1, albumin 35.6 g L-1, globulins 20.3 g L-1, urea 5.37 mmol L-1, Ca 2.56 mmol L-1, P 1.81 mmol L-1, Mg 0.81 mmol L-1 and cortisol 34.1 nmol L-1. The only significant differences between the Hartón del Valle and the Holstein breeds were total protein, globulin and the serum cortisol levels. / En bovinos, el período de transición comprende las tres últimas semanas preparto y las primeras tres posparto. Es caracterizado por adaptaciones en el metabolismo de lípidos, carbohidratos, minerales y proteínas buscando compensar el bajo consumo de materia seca y el inicio de la secreción láctea; estos cambios son regulados por corticosteroides liberados al parto. Algunos metabolitos presentan en esta etapa cambios manifiestos en su concentración sanguínea que puede llevar a problemas sanitarios, reproductivos y productivos. El objetivo fue analizar la homeostasis en el período de transición a través de la determinación de la concentración de indicadores proteicos, y de algunos macrominerales, en vacas lecheras de dos grupos raciales en condiciones de trópico bajo. El trabajo se realizó en dos fincas comerciales con similares condiciones de manejo, en la región suroriental de Colombia, en zona agroecológica de bosque seco tropical según Holdridge (1987), a 1.050 msnm., temperatura promedio de 23 ºC y precipitación anual de 1.200 mm distribuida en forma bimodal; la alimentación se basó en pasto Estrella (Cynodon nlemfuensis). Se utilizaron siete vacas Holstein y siete vacas Hartón del Valle, de las cuales se obtuvieron muestras de sangre recolectadas por venipunción coccígea en tubos a vacío, con heparina como anticoagulante y sin anticoagulante, durante el período de transición y hasta el día 60 del posparto; se analizaron un total de 156 muestras. Se determinó: proteína total, albúmina, globulinas y urea; los macrominerales Ca, P y Mg, y la hormona cortisol. Los valores promedios encontrados fueron: proteínas totales 66,7 g L-1, albúmina 37,6 g L-1, globulinas 27,7 g L-1, urea 6,11 mmol L-1, Ca 2,21 mmol L-1, P 1,87 mmol L-1, Mg 1,03 mmol L-1 y cortisol 33,2 nmolL-1, para la raza Holstein. Para el grupo Hartón se encontró: proteínas totales 57,7 g L-1, albúmina 35,6 g L-1, globulinas 20,3 g L-1, urea 5,37 mmol L-1, Ca 2,56 mmol L-1, P 1,81 mmol L-1, Mg 0,81 mmol L-1 y cortisol 34,1 nmol L-1. Entre las razas Hartón del valle y Holstein sólo se presentaron diferencias significativas para proteínas totales, globulinas y en los niveles séricos de cortisol.